Impact of Blinatumomab Treatment on Bone Marrow Function in Patients with Relapsed/Refractory B-Cell Precursor Acute Lymphoblastic Leukemia - Hagop M. Kantarjian (MDPI AG, 2021)
Association of blinatumomab treatment with myelosuppression was examined in this study. Peripheral blood counts were assessed prior to, during, and after blinatumomab treatment in patients with relapsed/refractory Philadelphia chromosome-negative (Ph−) B-cell precursor (BCP) acute lymphoblastic leukemia (ALL; n = 267) and Ph+ BCP-ALL (n = 45) from the TOWER and ALCANTARA studies, respectively, or chemotherapy in patients with Ph− BCP-ALL (n = 109) from the TOWER study; all the patients with relapsed/refractory BCP-ALL and responders achieving complete remission (CR) or CR with partial/incomplete hematological recovery (CRh/CRi) were evaluated. Event-free survival (EFS) and overall survival (OS) were assessed in patients achieving CR and CRh/CRi. Median leukocyte, neutrophil, and platelet counts increased during two blinatumomab cycles but remained low longer after chemotherapy. Among the responders, there was a trend that a greater proportion of patients achieved CR with blinatumomab (Ph−, 76.5%; Ph+, 77.8%) versus with chemotherapy (Ph−, 63.6%). In the TOWER study, the survival prognosis for patients achieving CRh/CRi versus CR with blinatumomab was more similar (median OS, 11.9 (95% CI, 3.9–not estimable (NE)) vs. 15.0 (95% CI, 10.4–NE) months, p = 0.062) than with chemotherapy (5.2 (95% CI, 1.6–NE) vs. 18.9 (95% CI, 9.3–NE) months, p = 0.013). Blinatumomab treatment, with only temporary and transient myelosuppression, resulted in a greater survival benefit than chemotherapy.